THE INFLUENCE OF ROLE STRESS AND TIME LIMITED INTERNAL AUDITOR ON INTERNAL CONTROL UNIT PERFORMANCEâ€ - Yulianti, Maria Lusiana (Universitas Pendidikan Indonesia, 2021)
This research investigates the significant effect of internal auditorâ€™s role stress upon the performance of internal audit. There are two factor used to measure the value of internal auditorâ€™s role stress : role conflict and role ambiguity. While indicators to measure Time Limited internal auditors, the auditors used the time attitude and attitude auditors audit the audit quality loss .Meanwhile, internal auditor performance variable measured by pursuant to internal professional practice norm of auditor consisted of five indicators that is independency, professional ability, work scope, execution of activity of inspection and internal audit management.The research method used in causal method with survey approach. The data were collected through questionnaires sent to 30 internal auditor from internal control unit PT Kereta Api Indonesia ( Persero ) yang bertempat di Jl.Perintis Kemerdekaan No.1 Bandung.The resultsofthis research indicatethat theroleof stress and time limited auditors in the Internal Audit Unit of PT Kereta Api Indonesia (Persero) is neither category. And the performance of the Internal Audit Unit Audit of PT Kereta Api Indonesia (Persero) in the categoryenough. Partially and simultaneously, Role Stressand Time Limited Auditor havean influence on the performance of Internal Auditorat PT KeretaApi Indonesia (Persero). The magnitude ofthe effect of Role Stress and Time Limited Auditors on the performance of the internal auditor sis 58,8%. While the remaining 41.2% is contributed by other variables besides Role Stress and Limitation of Time / TimeLimited.Â Keywords : Role Stress;Â Time Limited; Internal Audit; Performance.